ANALISIS SINTESIS PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PERKEMBANGAN MORAL PESERTA DIDIK SEKOLAH DASAR - Fransisca Ayu Prasetyo Murti; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid rise of digital technology, particularly social media, has fundamentally reshaped the moral landscape of elementary school students. This study synthesizes existing research to unpack both the positive and negative sides of social media usage on young learners' moral development, viewed through established psychological lenses. Using a research synthesis approach, we analyzed 10 selected scientific articles published between 2021 and 2025. The findings reveal a double-edged sword: on the flip side, unmonitored screen time on platforms like TikTok and Instagram triggers behavioral issues, such as a decline in politeness, poor online etiquette, and a tendency to mimic negative trends. On the bright side, when parents and teachers step in to guide them, social media can actually boost learning motivation, sharpen self-regulation, and help children internalize positive moral and spiritual values. Ultimately, because children at this age are highly impressionable, equipping them with digital literacy and embedding character education into school culture are absolutely critical to steering their digital habits in a positive direction.